Exposure to common infections may shape basal immunity and potentially HIV-1 acquisition amongst a high-risk population in Coastal Kenya - Fwambah, Lynn; Andisi, Cheryl; Streatfield, Claire; Bromell, Rachel; Hare, Jonathan; Esbjörnsson, Joakim; Ndung’u, Thumbi; Sanders, Eduard J.; Hassan, Amin S.; Nduati, Eunice (Frontiers in Immunology, 2024)
The impact of exposure to endemic infections on basal immunity and susceptibility to HIV-1 acquisition remains uncertain. We hypothesized that exposure to infections such as cytomegalovirus (CMV), malaria and sexually transmitted infections (STIs) in high-risk individuals may modulate immunity and subsequently increase susceptibility to HIV-1 acquisition. A case-control study nested in an HIV-1 negative high-risk cohort from Coastal Kenya was used. Cases were defined as volunteers who tested HIV-1 positive during follow-up and had a plasma sample collected 3 ± 2 months prior to the estimated date of HIV-1 infection. Controls were individuals who remained HIV-1 negative during the follow-up and were matched 2:1 to cases by sex, age, risk group and follow-up time. STI screening was performed using microscopic and serologic tests. HIV-1 pre-infection plasma samples were used to determined exposure to CMV and malaria using enzyme-linked immunosorbent assays and to quantify forty-one cytokines and soluble factors using multiplexing assays. Multiplexing data were analyzed using principal component analysis. Associations between cytokines and soluble factors with subsequent HIV-1 acquisition were determined using conditional logistic regression models. Overall, samples from 47 cases and 94 controls were analyzed. While exposure to malaria (p=0.675) and CMV (p=0.470) were not associated with HIV-1 acquisition, exposure to STIs was (48% [95% CI, vs. 26% [95% CI,]. Ten analytes were significantly altered in cases compared to